2019
DOI: 10.1038/s41550-019-0885-x
|View full text |Cite
|
Sign up to set email alerts
|

Ferrovolcanism on metal worlds and the origin of pallasites

Abstract: As differentiated planetesimals cool, their cores can solidify from the outside-in1, as evidenced by paleomagnetic measurements and cooling rate estimates of iron meteorites2,3.The details of outside-in solidification and fate of residual core melt are poorly understood.For a core primarily composed of Fe and Ni alloyed with lighter constituent elements, like sulfur, such inward core growth would likely be achieved by growth of solid FeNi dendrites4. Growth of FeNi dendrites results in interconnected pockets o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
77
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(86 citation statements)
references
References 28 publications
9
77
0
Order By: Relevance
“…An intact iron‐nickel metal core would have nearly twice the density of Psyche, as summarized in this paper. However, the density requirement is achieved if Psyche is either a rubble pile with significant porosity, or if it retains 25 to 80 km of silicate rock on its surface (Johnson et al, ), or if it is greatly enriched in sulfur. Having a fully silicate surface is likely precluded by the radar reflectance data, which implies that the interior is also at least partially metallic.…”
Section: Planetesimal Formation and Evolution Scenariosmentioning
confidence: 99%
“…An intact iron‐nickel metal core would have nearly twice the density of Psyche, as summarized in this paper. However, the density requirement is achieved if Psyche is either a rubble pile with significant porosity, or if it retains 25 to 80 km of silicate rock on its surface (Johnson et al, ), or if it is greatly enriched in sulfur. Having a fully silicate surface is likely precluded by the radar reflectance data, which implies that the interior is also at least partially metallic.…”
Section: Planetesimal Formation and Evolution Scenariosmentioning
confidence: 99%
“…Alternatively, Psyche's density appears compatible with that of stony-iron meteorites such as mesosiderites (Viikinkoski et al 2018) and pallasites (Elkins-Tanton et al 2020) as well as that of CB chondrites (Elkins-Tanton et al 2020). Recently, Johnson et al (2020) proposed that Psyche formed as a differentiated body and that ferrovolcanism could be at the origin of the high metal content of its surface (Shepard et al 2017). As of today, it is not understood whether Psyche formed as a differentiated or undifferentiated body.…”
Section: Introductionmentioning
confidence: 99%
“…The dunite layer was modeled as in scenario (a), while the iron core was modeled as either an intact core (scenario b) or a shattered, porous core (scenario c). Impacts into a dunite mantle covered by a thin iron layer. One hypothesis that may explain the observed elevated metal content on Psyche's surface is the presence of a thin iron layer covering the mantle as a result of ferrovolcanism (Abrahams & Nimmo, 2019; Johnson et al, 2019). During the cooling period of proto‐Psyche, compressional stresses produced in the cooling crust were relieved by faults, allowing Fe‐Ni rich material from the core to propagate to the surface in dikes.…”
Section: Numerical Modelmentioning
confidence: 99%
“…Abrahams and Nimmo (2019) proposed that repeated ferrovolcanic eruptions on a fully metallic asteroid would be able to raise enough molten iron material to the surface to cover a more dense iron shell. Johnson et al (2019) showed that ferrovolcanic eruptions are also possible on iron asteroids covered by a thin mantle; however, an estimate of the amount of molten iron erupted was not given. Therefore, here we assumed that the impacts occurred after the iron melt cooled and formed a 50‐m layer covering the mantle.…”
Section: Numerical Modelmentioning
confidence: 99%
See 1 more Smart Citation